Viral capture sequencing detects unexpected viruses in the cerebrospinal fluid of adults with meningitis. Issue 4 (April 2022) - McGill, Fiona; Tokarz, Rafal; Thomson, Emma C; Filipe, Ana; Sameroff, Stephen; Jain, Komal; Bhuva, Nishit; Ashraf, Shirin; Lipkin, W. Ian; Corless, Caroline; Pattabiraman, Chitra; Gibney, Barry; et al.
Highlights: Viral capture sequencing detected a virus in 42% of patients with meningitis. Potentially pathogenic virus detected in 68% of those. Capture sequencing allows detection of unexpected pathogens. Abstract: Objectives: Many patients with meningitis have no aetiology identified leading to unnecessary antimicrobials and prolonged hospitalisation. We used viral capture sequencing to identify possible pathogenic viruses in adults with community-acquired meningitis. Methods: Cerebrospinal fluid (CSF) from 73 patients was tested by VirCapSeq-VERT, a probe set designed to capture viral targets using high throughput sequencing. Patients were categorised as suspected viral meningitis – CSF pleocytosis, no pathogen identified ( n  = 38), proven viral meningitis – CSF pleocytosis with a pathogen identified ( n  = 15) or not meningitis – no CSF pleocytosis ( n  = 20). Results: VirCapSeq-VERT detected virus in the CSF of 16/38 (42%) of those with suspected viral meningitis, including twelve individual viruses. A potentially clinically relevant virus was detected in 9/16 (56%). Unexpectedly Toscana virus, rotavirus and Saffold virus were detected and assessed to be potential causative agents . Conclusion: VirCapSeq-VERT increases the probability of detecting a virus. Using this agnostic approach we identified Toscana virus and, for the first time in adults, rotavirus and Saffold virus, as potential causative agents in adult meningitis. Further work is needed to determine the prevalence of atypical viral candidates as well as the clinical impact of using sequencing methods in real time. This knowledge can help to reduce antimicrobial use and hospitalisations leading to both patient and health system benefits.